User attitudes towards virtual home assessment technologies. (18th August 2022) - Lanfranchi, V.; Jones, N.; Read, J.; Fegan, C.; Field, B.; Simpson, E.; Revitt, C.; Cudd, P.; Ciravegna, F.
Abstract: Telehealth has long been highlighted as a way to solve issues of efficiency and effectiveness in healthcare and to improve patients' care and has become fundamental to address patients' needs during the COVID-19 pandemic; however previous studies have shown mixed results in the user acceptance of such technologies. Whilst many previous studies have focussed on clinical application of telehealth, we focus on the adoption of telehealth for virtual assessments visits aimed to evaluate the suitability of a property where a patient is discharged, and eventual adaptations needed. We present a study of stakeholders' attitudes towards such virtual assessment visits. The study has been carried out with healthcare professionals and patients and allowed us to identify user attitudes, barriers and facilitators for the success of virtual assessment visits from the point of view of healthcare professionals and patients. Finally, we discuss implications for designers of telehealth services and guidelines that can be derived from our study.